Thermal degradation kinetics of polyimide nanocomposites from different carbon nanofillers: Applicability of different theoretical models. Issue 7 (13th October 2017) - Nayak, Lalatendu; Rahaman, Mostafizur; Khastgir, Dipak; Chaki, Tapan Kumar
ABSTRACT: In this study, the nanocomposites of polyimide (PI) with the nanofillers multiwalled carbon nanotube (MWCNT) and carbon nanofiber (CNF) were prepared by in situ polymerization technique. The thermal stability of the nanocomposites were investigated and discussed with respect to nanofillers type, concentration, and their functionality within the PI matrix. It is observed that there are 16 and 18 °C increment in thermal degradation temperature with the addition of 3 wt % MWCNT and CNF within the PI matrix, respectively. The thermal degradation kinetics of the nanocomposites were studied by Kissinger–Akahira–Sunose method, Flynn–Wall–Ozawa method, and Kim–Park method. The results show that these models are well fitted with the experimental data. It is found that the calculated activation energy increases with the increase in nanofillers loading and PI/CNF nanocomposites exhibit higher activation energy compared to PI/MWCNT composites at their similar loading. Moreover, the effect of nanofillers type and loading on the glass transition temperature of nanocomposites were also investigated in details. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45862. Abstract :